2017
DOI: 10.1039/c7ra03912c
|View full text |Cite
|
Sign up to set email alerts
|

Integrating metallic nanoparticles of Au and Pt with MoS2–CdS hybrids for high-efficient photocatalytic hydrogen generation via plasmon-induced electron and energy transfer

Abstract: A mechanism of high-efficient photocatalytic hydrogen generation via plasmon-induced electron and energy transfer was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 70 publications
(145 reference statements)
0
19
0
Order By: Relevance
“…Among all samples, LaMoS 2 with lanthanum loading of 3% exhibited best photocatalytic efficiency achieving total H 2 yield of 110 μmol/h in 6 hours of visible light illumination and is 5.2 times higher as compared to pure MoS 2 (20 μmol/h). This type of excellent photocatalytic performance could be attributed to lanthanum doping, which facilitates the transfer of charge carrier and prolonged electron life times as confirmed by PL measurement (Figure ). Interestingly, the performance of prepared 3D flower‐like 3%LaMoS 2 photocatalyst was found much higher than other photocatalysts recently investigated by different researchers as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Among all samples, LaMoS 2 with lanthanum loading of 3% exhibited best photocatalytic efficiency achieving total H 2 yield of 110 μmol/h in 6 hours of visible light illumination and is 5.2 times higher as compared to pure MoS 2 (20 μmol/h). This type of excellent photocatalytic performance could be attributed to lanthanum doping, which facilitates the transfer of charge carrier and prolonged electron life times as confirmed by PL measurement (Figure ). Interestingly, the performance of prepared 3D flower‐like 3%LaMoS 2 photocatalyst was found much higher than other photocatalysts recently investigated by different researchers as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…As a direct bandgap semiconductor, monolayer MoS 2 possesses excellent mechanical and optoelectronic properties, including flexibility, strong light–matter interaction, and optical absorption in the visible light region. , However, MoS 2 alone exhibits negligible photocatalytic activity due to inefficient charge separation and the presence of defects. The latter disadvantage can be viewed as an advantage for a traditional thermal catalyst, , because the defects, acting as active sites, are beneficial for the hydrogen evolution reaction. ,, To be utilized as an efficient photocatalyst, composites of MoS 2 with other materials, such as metallic nanoparticles, semiconducting quantum dots, , graphene, ,,, etc., show great promise in boosting solar hydrogen production. Compared to rigid nanostructured particles, graphene holds many advantages, including a large surface for improved interfacial contact, high electronic conductivity for charge transport, and excellent flexible and stretchable properties for self-adaptive compatibility of transition metal dichalcogenides (TMDs). Given the synergistic effects of two materials, the graphene–MoS 2 hybrid systems show high visible light photocatalytic activity for splitting water to produce hydrogen. ,, Min et al reported that the composites of either reduced graphene oxide sheets or graphene with MoS 2 facilitate charge separation by promoting the transfer of photoexcited electrons and inhibit charge recombination, and even decrease charge transfer resistance, thereby improving the photocatalytic hydrogen evolution efficiency.…”
mentioning
confidence: 99%
“…Due to the presence of the common S 2– anions and defects on the surface of octahedrons, the surface nucleation energy of octahedrons is very lower. Au will nucleate more easily on the surface of the nanooctahedrons, and then the Au will cover the surface of octahedrons, while very little amount of Au grow into nanoparticles on its own. , Au nanocups are selectively overgrown on one vertex of the CdS–PbS nanooctahedrons. The magnified TEM image of Au@CdS–PbS presented in Figure S1 shows the detailed structure which consists of a Au nanocup and a CdS–PbS nanooctahedron.…”
Section: Resultsmentioning
confidence: 99%